Fluxo informacional no acompanhamento de projetos arquitetônicos: proposta de protótipo de sistema de informação para instituição de ensino superior - Nunes, Reginaldo Barboza (2021)
Within the scope of the Federal University of Rio Grande do Norte (UFRN), the Infrastructure Superintendence (INFRA) has successfully accomplished projects for new buildings that may involve tens of thousands of m2 of built area and tens of millions of reais in value of effort. Such magnitude and complexity demand high capacity in the information management of these projects through information systems (IS) due to their relevant role in monitoring the process of preparing architectural projects, in presenting valuable information, during the development of projects, and in the analysis of all its informational flow. In this way, it is opportune for the organization to have an IS integrated with the management of the projects, allowing the available resources to be applied efficiently and effectively. In view of this organizational context, it is relevant to ask: “how can the information flow integrated into an information system contribute to improving the monitoring of the process of elaborating INFRA's architectural projects?”. To answer this problem, an applied, descriptive, and qualitative research was developed, with the research strategy of conducting a single case study. As a method of data collection, five semi-structured interviews were conducted with managers and specialists from the sector in question, in addition to the use of documentary research. Data analysis was carried out through thematic analysis based on the theoretical-conceptual framework conceived through the theoretical foundation. As a result, the research pointed to the existence of an informal and inappropriate information flow for the elaboration of architectural projects at INFRA, the non-adherence of the Infrastructure module of the Integrated Patrimony, Administration and Contracts System (SIPAC) to the information flow detected and suggested aspects of improvement for an integrative information flow. Thus, it was proposed a prototype, at a conceptual level, of an information system module to support the flow of information adequate to accompany the process of elaboration of architectural projects. It is expected that, based on the elaborated prototype, the institution will be able to implement it to further increase its competence in the information management of new building construction projects.